Studi Literatur Pengaruh Manajemen Program dan Sarana Prasarana Terhadap Layanan Bimbingan dan Konseling di Sekolah: Manajemen Program dan Sarana Prasarana Layanan Bimbingan Dan Konseling - fitri, nur kholiza (SHINE: JURNAL BIMBINGAN DAN KONSELING, 2025)
Guidance and counseling has a essential function in aiding student development, both in academic, social, emotional, and career aspects. To ensure the effectiveness of BK services, good management and adequate facilities and infrastructure are needed. This research focuses on evaluating the consequences of BK management and the significance of facilities and infrastructure in enhancing the standard of school services. The approach Utilized is a literature review, examining different sources connected to the planning, organizing, implementation, and evaluation of BK management, In addition to the role of facilities such as well-equipped counseling rooms and tools in boosting service effectiveness. The findings suggest that well-structured BK management and proper management of facilities and infrastructure can enhance the quality of counseling services and foster an environment that assists students in overcoming challenges. On the other hand, insufficient support in management and facilities can hinder the effectiveness of BK services. This research recommends improvements in management and the provision of more sufficient facilities and infrastructure to support the success of guidance and counseling services in schools.